Circadian influences on myocardial infarction - Virag, Jitka A. I.; Lust, Robert M. (Frontiers in Physiology, 2014)
Components of circadian rhythm maintenance, or “clock genes,” are endogenous entrainable oscillations of about 24 h that regulate biological processes and are found in the suprachaismatic nucleus (SCN) and many peripheral tissues, including the heart. They are influenced by external cues, or Zeitgebers, such as light and heat, and can influence such diverse phenomena as cytokine expression immune cells, metabolic activity of cardiac myocytes, and vasodilator regulation by vascular endothelial cells. While it is known that the central master clock in the SCN synchronizes peripheral physiologic rhythms, the mechanisms by which the information is transmitted are complex and may include hormonal, metabolic, and neuronal inputs. Whether circadian patterns are causally related to the observed periodicity of events, or whether they are simply epi-phenomena is not well established, but a few studies suggest that the circadian effects likely are real in their impact on myocardial infarct incidence. Cycle disturbances may be harbingers of predisposition and subsequent response to acute and chronic cardiac injury, and identifying the complex interactions of circadian rhythms and myocardial infarction may provide insights into possible preventative and therapeutic strategies for susceptible populations.